The Relationship between Pharmaceutical Services and BPJS Patient Satisfaction at the Wijaya Kusuma Clinic, Tangerang - Arief, Ilham; L.M. Zulfahrin UZ; Sidabutar, Sulastri (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The purpose of this research is to ascertain whether or not the Wijaya Kusuma Clinic's pharmaceutical services correlate with the level of pleasure its BPJS patients report. The data for this study was collected using a quantitative survey method. Outpatients who participated in BPJS Kesehatan at the Wijaya Kusuma Clinic in Tangerang were asked to fill out questionnaires using Google Forms. All patients receiving BPJS as outpatients made up the study population. We used a combination of the non-probability sampling technique and the purposive selection type to select 328 participants for the study. We processed the data using Ms. Excel 2010 and IBM SPSS Statistics version 29. The study's results revealed that the average age of BPJS patients treated in January 2024 was 26-55 years, with a majority of women at 62.5% and male patients at 37.5%. The patient satisfaction survey revealed that 2.1% of respondents were less satisfied, 43.0% were quite happy, 35.4% were satisfied, and 19.5% were delighted. Therefore, we can conclude that a significant proportion of patient satisfaction respondents fell into the